QoS provisioning in cellular networks using environment based interference alleviation model. (8th May 2012) - Karia, Deepak C.; Lande, B.K.; Daruwala, R.D.
QoS in cellular networks depends on various parameters, where Carrier-to- Interference Ratio (CIR) is one of the fundamental parameters amongst the others. This in turn depends on power transmitted by the Base Stations (BS) and interference which actually is the power radiated out by the unwanted sources, making optimum allocation of power the foremost important design metric. In this paper, we propose a novel approach for which various distributed power control algorithms are studied extensively. To validate the proposed models, the central focus of the paper is to maintain the CIR close to the threshold value, which is predefined. The models consider shadowing and also interference to modulate the transmitted power, which tunes according to the dominating environmental conditions and are independent from the point of view of specifying the upper and lower bounds of the transmitted power in order to maintain the achieved optimum power in a feasible domain.